Regional Sustainable Development through the Cohesion Fund: The Case of the Water and Wastewater Infrastructure in the County of Satu Mare - Porumbăcean, Claudiu; Lașan, Nicoleta (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Since the entry into force of the Treaty of Maastricht in November 1993, strengthening the economic and social cohesion has officially become one of the main objectives of the new European Union, alongside with the establishment of the internal market and the creation of the Economic and Monetary Union. In 1994 the European Union members states decided to create the Cohesion Fund which aims to support projects in the field of environment protection and transport infrastructure in less developed member states. The biggest project currently being implemented in the County of Satu Mare is co-financed from the Cohesion Fund via the "Environment" Operational Program and aims to improve the quality and access to water and wastewater infrastructure, a sector in deep need of investments in post-communist Romania. The project, having a total value of more than â‚¬100 million, continues the investments made from the ISPA measure in the pre-accession period and will be followed during the next financial programming period by a new application. In this context, the paper aims to assess the evolution of the funds allocated from the Cohesion Fund for major investments in the water and wastewater sector in the County of Satu Mare using the data provided by the regional operator and the analyses made by the Managing Authority. Furthermore, we consider important to underline the main obstacles and problems that beneficiaries have to face with when they apply for and implement projects that lead in the end to regional sustainable development.